2017
DOI: 10.5301/hipint.5000534
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised comparison of 2 skin closure techniques in primary total hip arthroplasty surgery

Abstract: Closure with running subcuticular suture is cheaper and appears to have a clinical advantage when compared with metallic staples skin closure in primary THA surgery. However, additional operating time may be incurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…Only one RCT (7.7%) reported significant findings. Rui et al 56 compared staples versus absorbable subcuticular suture for skin closure at a 3-month follow-up in 165 patients. They reported no infections in sutures group versus 2 superficial infections (2.4%) in the staples group.…”
Section: Resultsmentioning
confidence: 99%
“…Only one RCT (7.7%) reported significant findings. Rui et al 56 compared staples versus absorbable subcuticular suture for skin closure at a 3-month follow-up in 165 patients. They reported no infections in sutures group versus 2 superficial infections (2.4%) in the staples group.…”
Section: Resultsmentioning
confidence: 99%
“…These potential risk factors for SSI would suggest the need for adjusted or subgroup analysis; however, they were not performed, thus limiting confidence in the two currently available systematic review and meta-analyses. Furthermore, since the most recent meta-analysis [20], several additional randomized controlled trials (RCTs) have been identified [3,11,15,16,23,26,29]. Consequently, an updated meta-analysis is warranted to assess whether current RCT evidence supports the superiority of staples or sutures for wound closure after orthopaedic surgery, or whether more research is needed before definitive clinical recommendations can be made regarding SSI reduction.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition to surgical technique and comorbidities, a few studies have evaluated the method of incision closure following THA as a possible risk factor for wound complications. [7][8][9][10][11] The majority of these studies compare staples with either skin adhesive or sutures, but are inconclusive in their results. [7][8][9][10] Furthermore, these studies specifically examine the posterior 11 or lateral approaches, 10 or a combination of anterolateral and posterolateral.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] The majority of these studies compare staples with either skin adhesive or sutures, but are inconclusive in their results. [7][8][9][10] Furthermore, these studies specifically examine the posterior 11 or lateral approaches, 10 or a combination of anterolateral and posterolateral. 8,9 To our knowledge, there is currently no study evaluating incision closure technique as a cause for wound complications following THA via the DAA.…”
mentioning
confidence: 99%
See 1 more Smart Citation